Racial Disparities in In-Hospital Adverse Events Among Patients With Atrial Fibrillation Implanted With a Watchman Left Atrial Appendage Occlusion Device: A US National Perspective. (18th May 2021) - Khan, Muhammad Zia; Munir, Muhammad Bilal; Darden, Douglas; Pasupula, Deepak Kumar; Balla, Sudarshan; Han, Frederick T.; Reeves, Ryan; Hsu, Jonathan C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Left atrial appendage occlusion using a Watchman device has shown promise in reducing stroke risk in selected atrial fibrillation patients. Limited data exist on differences in characteristics and in-hospital outcomes of Watchman recipients in the United States based on race/ethnicity. Methods: Data were extracted from the National Inpatient Sample database for calendar years 2015 to 2018. The study sample was stratified into 4 groups (White, Black, Hispanic, and other races). Baseline characteristics, procedural complications, and key in-hospital outcomes were then assessed. We also analyzed the independent association of race/ethnicity with key in-hospital outcomes including major complications, prolonged hospital stay, and increased hospitalization cost. Results: A total of 34 960 Watchman recipients were included in the final analysis. Black and Hispanic patients had higher prevalence of heart failure, hypertension, obesity, and renal failure when compared with White patients. The crude rate of overall procedural complications was also higher in Blacks, Hispanics, and patients of other race when compared with White patients (15.2%, 12.4%, and 14.1% versus 9.9%; P <0.01). After multivariable adjustment, compared with White patients, Blacks, Hispanics, and patients of other race experienced a higher likelihood of a major complication from the procedure (adjusted odds ratio, 1.223 [95% CI, 0.986–1.517], 1.296 [95% CI, 1.075–1.561], and 1.924 [95% CI, 1.569–2.360], respectively) and prolonged length of stay >1 day (adjusted odds ratio, 1.631 [95% CI, 1.431–1.859], 1.239 [95% CI, 1.110–1.383], and 1.619 [95% CI, 1.403–1.869], respectively). Conclusions: Non-White patients undergoing Watchman implantation had higher prevalence of key comorbidities and also experienced increased Watchman-related adverse events including procedural complications and prolonged length of stay, even after adjustment for potential confounders. Further research is needed to identify etiologies behind differential outcomes among non-White patients after Watchman implantation.